Analysis of the Influence of the Amount of Aid Funds, Regulations, and the Size of Political Parties on the Compliance of Financial Information Disclosure via the Internet (Internet Financial Reporting) - Ghina Sausan Fadiyah; Vidyarto Nugroho (Green Publisher Indonesia, 2026)
This research aimed to empirically examine the influence of the amount of assistance funds, regulations, and political party size on compliance with Internet-based financial information disclosure (Internet Financial Reporting [IFR]) among national political parties in Indonesia, as well as to test the moderating role of political party size. This study employed a quantitative causal-associative design using Binary Logistic Regression on 45 panel observations from nine national political parties during the 2020–2024 period, selected through purposive sampling. Data were obtained from BPK audit reports, KPU decisions, and official party websites, and analyzed using EViews 9. The results showed that the amount of assistance funds had a positive and significant effect on IFR disclosure compliance, with a coefficient of +30.5824 and a p-value of 0.0369, while regulations did not have a significant effect, with a coefficient of +0.1600 and a p-value of 0.8157. Political party size had a positive and significant effect on IFR disclosure compliance, with a coefficient of +146.3055 and a p-value of 0.0436. Furthermore, political party size moderated the relationship between assistance funds and IFR disclosure compliance, with a negative moderating effect indicated by a coefficient of −6.3926 and a p-value of 0.0406. The model produced a McFadden R-squared value of 0.1793 and a prediction accuracy rate of 64.44%. These findings indicate that IFR compliance is influenced by stewardship responsibilities and public visibility pressures, whereas formal regulations alone are insufficient to encourage substantive behavioral changes. The negative moderating effect suggests the presence of diminishing returns and potential bureaucratic inertia within larger political parties.